Connections between arc volcanoes in Central Kamchatka and the subducting slab inferred from local earthquake seismic tomography - Bushenkova N.A.; Koulakov I.Yu.; Bergal-Kuvikas Olga; Shapiro Nikolay M.; Gordeev E.I.; Chebrov D.V.; Abkadyrov Ilyas; Jakovlev Andrey; Stupina Tatiana; Novgorodova A.; Droznina S.Ya.; Huang H. (My University, 2023)
The area of Central Kamchatka limited by latitudes of 52.5 and 54 degrees includes six active volcanoes (Avacha, Koryaksky, Zhupanovsky, Mutnovsky, Gorely and Opala), as well as a number of dormant and extinct stratovolcanoes, monogenic cones and large calderas. Furthermore, it contains the Malko-Petropavlovsk fracture zone (MPZ), which marks the boundary between two distinct subduction regimes to the south and to the north. We present a new seismic tomography model for this area, which was constructed based on the joint use of data of the Kamchatkan permanent seismic stations and a temporary network installed in the region in 2019–2020. A series of synthetic tests have demonstrated fair resolution of the derived seismic velocity structures in the crust and in the mantle wedge down to ~150 km. The distributions of the P and S wave velocities, and especially the Vp/Vs ratio, clearly highlight the connection between the volcanic centers in Central Kamchatka and the subducting slab. At depths below 40 km depth, we observe two large low-velocity anomalies centered below Zhupanovsky and Mutnovsky volcanoes and covering all other volcanoes in the area. In the vertical sections, the corresponding anomalies of high Vp/Vs ratio have mushroom shapes with the heads spreading along the bottom of the crust, which probably represent the underplating of magma material that feeds the volcanoes of the groups. The tomography results also reveal some important tectonic features, such as a V-shaped fault system in the Avacha Graben, which is the part of the MPZ.
Keywords: 38.37.25 Вулканология; Асача; Бакенинг; Бархатная Сопка; Авачинский; Горелый; Корякский; Козельский; Мутновский; Вилючинский; Заварицкого; Жупановский